(untitled) (El-Wahat Journal for Research and Studies, 2021)
The Statistical Study Of The Major Constituents Of The Saharan Tourism Has Taken Up A Crucial Importance Regarding The High And Worldly Quality Touristic Outcomes Emanating From Various Areas In Algeria’s Desert As Is The Case Of The District Of Ghardaia. This Area’s Touristic Diversity Has Got Unique Natural, Environmental And Sociocultural Specifications Because It Allows The Tourists To Enjoy Discovering The Tangible Touristic Potentials As Well The As The Non-Tangible Ones That Reflect The Link Between The Man’s Life Styles And His Saharan Environment. This Is Fleshed Out By The Findings Of This Study Considering The Records On The Touristic Development In The Area, Among Which We Can Cite A Total Of 25 Tourist Receptions And Orientation Facilities Such As Hotels As Well As Ranked And Unranked Residential Centers Plus 25 Travel Agencies. Moreover, The Number Of Registered Tourists Whether From Inland Or Foreign Tourists Has Increased And Job Opportunities In The Area Have Soared To 4,9% Of The Total Number Of Filled Jobs. Despite The Increasing Attention Paid To The Local Touristic Market In Ghardaia And Creating More Chances For The Touristic Investment Which, When Compared To Other Sectors, Don’t Exceed 19 % Of The Total Number Of 521 Investment Projects. Therefore, The Exploitation Of Such Civilizational And Historic Components Relevant To The Area Must Be Extended Along With The Creation Of Modern Projects That Should Be Inspired From The Reality At Hand And The Future Touristic Developmental Aspirations At Local And National Levels. Key Words, Tourism, Touristic Potentials, The Saharan Tourism, Tourists Flow.